Design of Quantum Communication Protocols in Quantum Cryptography - Alhayani, Bilal A.; AlKawak, Omar A.; Mahajan, Hemant B.; Ilhan, Haci; Qasem, Roa'a Mohammed (SPRINGER, 2023)
Secure communication has developed into one of the most promising disciplines in the contemporary world. This is a highly essential subject for every business and body, and its advancements are increasing significantly. Quantum computing is becoming an increasingly popular kind of contemporary computing. This type of computing makes advantage of the fundamental characteristics of quantum mechanics to process information. Certain of the problems that were present in classical computing, such as the factoring discrete logarithm problem, have already been addressed by some writers in the field of quantum computing QC. Another significant challenge faced by conventional computing is one related to security, which may now be addressed thanks to quantum cryptography protocols. However, researchers have recently shown that even quantum encryption may be vulnerable to hacking. Implementing protocols for quantum cryptography still comes with a number of significant challenges, the most significant of which being quantum bit errors.
Keywords: Quantum communication; Quantum cryptography; Physical sciences; TELEPORTATION; STATE; Telecommunications